Lack of Association between Recurrent Pregnancy Loss and Inherited Thrombophilia in Hispanic Patients from Colombia (2004)
ABSTRACT: Introduction: Several genetic defects of coagulation factors have been implicated as a possible cause of recurrent pregnancy loss in Caucasians. The role of inherited thrombophilia as a risk factor in populations of Hispanic origin affected with this clinical condition is unknown. To our knowledge, this is the first study conducted to evaluate this genetic predisposition in Hispanics.